VERIFICATION OF THE DETERMINATION OF 12 MEV ELECTRON BEAM OUTPUT VERSA HD / 154714 LINEAR SPEEDING PLANE IN MAYAPADA HOSPITAL - Assef Firmando Firmansyah (Jurnal Forum Nuklir, 2020)
VERIFICATION OF THE DETERMINATION OF THE NOMINAL ENERGY BEAM OUTPUT OF THE 12 MEV LINEAR ACCELERATOR PLANE ELEKTA VERSA HD / 154714 AT MAYAPADA HOSPITAL. This paper describes verifying the determination of the 12 MeV nominal energy beam electron water absorption dose emitted from the Elekta Versa HD / 154714 medical linear accelerator owned by Mayapada Hospital, Lebak Bulus, Jakarta. Measurements were done in the 1D water phantom Scanner under reference conditions with the distance of the radiation source to the surface of the water 100 cm and the radiation field formed by the applicator 10 cm x 10 cm and the depth corresponding to (0.6 R50 - 0.1) cm. The IBA CC13 ionization detector is used as a radiation measurement tool for PDD measurements, while the Roos parallel ionization detector is used for absolute measurements. Roos's parallel ionizer detector is aligned with PTKMR-BATAN's PTW Webline electrometer. This detector is also traced to the primary standard laboratory of BIPM, France. Meanwhile, the PCC04 chip ionizing detector parallel to the PCC04 is coupled with a Dose 1 electrometer owned by Mayapada Hospital, which is traced to the PTB primary standard laboratory. Calculation of measurement results is carried out using the IAEA dosimetry protocol contained in Technical Report Series No. 398. The results obtained indicate a fairly good fit between the two measurements with a difference of 0.3%